Prognostic Value of Early Postoperative Troponin T in Patients Undergoing Coronary Artery Bypass Grafting. Issue 5 (27th February 2018) - Gahl, Brigitta; Göber, Volkhard; Odutayo, Ayodele; Tevaearai Stahel, Hendrik T.; da Costa, Bruno R.; Jakob, Stephan M.; Fiedler, G. Martin; Chan, Olivia; Carrel, Thierry P.; Jüni, Peter
Abstract : Background: Cardiac troponin T (cTnT) is elevated after coronary artery bypass grafting surgery. The aim of this study was to determine the association between cTnT elevations between 6 and 12 hours after coronary artery bypass grafting and in‐hospital outcome. Methods and Results: We prospectively studied 1722 patients undergoing isolated coronary artery bypass grafting. We assessed the association between conventional cTnT (749 patients) and high‐sensitivity cTnT (hs‐cTnT; 973 patients) 6 to 12 hours postoperatively with in‐hospital major adverse cardiac or cerebrovascular events (MACCE), a composite of all‐cause death, myocardial infarction, or stroke. The prespecified secondary outcome was a safety composite of MACCE, resuscitation, intensive care unit readmission or admission ≥48 hours, inotrope or vasopressor use ≥24 hours, or new‐onset renal insufficiency. Among patients with a conventional cTnT measurement, 92 experienced a MACCE (12%) and 146 experienced a safety composite event (19%). Likewise, for hs‐cTnT, 114 experienced a MACCE (12%) and 153 experienced a safety composite event (16%). Compared with cTnT ≤200 ng/L, each 200‐ng/L increment in cTnT was associated with a monotonous increase in the odds of MACCE and the safety composite outcome. Conventional and hs‐cTnT demonstrated moderate discrimination for MACCE (areas under the fitted receiver operating characteristics curve, 0.72 and 0.77 for conventional and hs‐cTnT, respectively) and the safety composite outcome (areas under the fitted receiver operating characteristics curve, 0.66 and 0.74 for conventional and hs‐cTnT, respectively) and resulted in improved prognostic performance when added to the EuroSCORE. At a cutoff of 800 ng/L, conventional and hs‐cTnT provided clinically relevant power to rule in MACCE and the safety composite outcome. Conclusions: cTnT levels assessed between 6 and 12 hours after coronary artery bypass grafting identify patients at increased risk of MACCE or other complications.